2016
DOI: 10.18632/oncotarget.13654
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic lethal killing of RAD54B-deficient colorectal cancer cells by PARP1 inhibition is enhanced with SOD1 inhibition

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related death throughout the world. Despite improved screening efforts, most CRCs are diagnosed at late stages when surgery alone is not curative. Moreover, the low 5-year survival rate (∼8-13%) for those living with stage IV CRC highlights the need for better treatment options. Many current chemotherapeutic approaches are non-specific and associated with side effects due to their tendency to target both normal and cancer cells. To address this issue, synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…23. 24 We have confirmed that RAD54B was associated with a decreased risk of NSOC in the present study. In the same period, RAD54B also showed abnormal expression in many cancer types, including colorectal cancer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…23. 24 We have confirmed that RAD54B was associated with a decreased risk of NSOC in the present study. In the same period, RAD54B also showed abnormal expression in many cancer types, including colorectal cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Its expression or function are pathogenic factors in the development and progression of cancer. 24 Subsequently, Chang et al 25 have confirmed that RAD54B could affect the prognosis of lung adenocarcinoma patients. These results revealed that RAD54B can not only lead to congenital malformations such as NSOC, but also play a role in the development of cancer by affecting genomic stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD54B represents an excellent candidate to exploit using a SL approach as it is somatically mutated or deleted in numerous cancer types (Figure A), and it encodes a protein with tumor suppressor‐like properties. Indeed, a number of genetic studies have already identified unique SL interactors for RAD54B including; (1) flap endonuclease‐1 ( FEN1 ), (2) superoxide dismutase 1 ( SOD1 ), (3) DNA Ligase IV ( LIG4 ), and (4) PARP1 …”
Section: Synthetic Genetic Targeting Of Rad54b Alterations In Cancer mentioning
confidence: 99%
“…Oh et al identified the SL interaction between RAD54B and LIG4 because the dual knockout of these genes resulted in no viable clones. Finally, McAndrew et al showed that RAD54B is SL with PARP1 and further showed that simultaneous inhibition of both PARP1 and SOD1 synergized and enhanced killing within a population of RAD54B ‐deficient cells …”
Section: Synthetic Genetic Targeting Of Rad54b Alterations In Cancer mentioning
confidence: 99%